2017
DOI: 10.1186/s12889-017-4897-0
|View full text |Cite
|
Sign up to set email alerts
|

Cultural factors associated with the intent to be screened for prostate cancer among adult men in a rural Kenyan community

Abstract: BackgroundThe aim of this study was to determine cultural factors associated with prostate cancer screening intent among adult Kenyan African men.MethodsA cross-sectional quantitative study with an analytic design was carried out in a randomly selected sample of 155 adult men aged 25–98 years living in a rural community in Kenya. Constructs from the Theory of Planned Behaviour were used to guide this study. A 5 -point Likert scale was used to assess fatalistic beliefs, fear, perceived benefits, and family infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
34
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 18 publications
11
34
3
Order By: Relevance
“…This implies that more effort needs to be made to increase awareness of the screening test and possibly facilities where it can be done. However, the findings of this study show better intention than another study done in Kenya [18] which revealed a lower intention of respondents to screen.…”
Section: Discussioncontrasting
confidence: 95%
“…This implies that more effort needs to be made to increase awareness of the screening test and possibly facilities where it can be done. However, the findings of this study show better intention than another study done in Kenya [18] which revealed a lower intention of respondents to screen.…”
Section: Discussioncontrasting
confidence: 95%
“…Our results are consistent with previous work on a wide variety of behaviours and traits in social networks [42][43][44], such as obesity [19,45], smoking [20,46], happiness [25], and vaccination and cancer screening participation [47][48][49]. In our study, having a tie was shown to play a role in the intention to screen among those with a positive screening intention.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that those with fatalistic views toward cancer are less likely to have accurate beliefs about cancer screenings, 20 are more likely to be unaware of or unengaged with cancer screening, 19 and have suggested that they believe the benefits of screening do not supersede their fatalistic views. 28 These authors' findings indicate that fatalistic cancer views may be a barrier to cancer screening. Barriers to cancer screenings for racial and ethnic minorities have been explored extensively.…”
Section: Discussionmentioning
confidence: 99%